In Search of Our Mothers’ Gardens: Alice Walker and the Analogical Imagination - Reineke, Martha J. (Philosophy & theology, 1988)
In this essay I offer a criticism of David Tracy’s work, The Analogical Imagination, in Iight of my reading of Alice Walker’s fiction. I propose that Tracy’s analysis of the contemporary theological scene is flawed because his portrait of theology bypasses important aspects of liberation theology. In particular, I suggest that despite Tracy’s rccognition of liberation theology, his work is imperiled by a residue of privilege that clings to his hermeneutic model of theology. As a consequence, opportunities for substantive dialogue with Iiberation theology are missed. The core of my criticism focuses on aspects of privilege that attend Tracy’s discussion of the religious classic. As I examine Alice Walker’s work. I suggest that Tracy would be disinclined to acccpt The Color Purple as a religious classic. His disinclination, I argue, may be attributed to three privileges: texts, time, and tradition. As I offer an alternative reading of the religious significance of The Color Purple, I suggest means by which explorations of a broader definition of “religious classic,” inclusive of works such as The Color Purple, might lead to productive dialogue between Tracy and liberation theologians.